2014
DOI: 10.1080/15332845.2015.955562
|View full text |Cite
|
Sign up to set email alerts
|

The Making of Hospitality Managers: The Role of Knowledge in the Development of Expertise

Abstract: This study examines the nature of hospitality managers' knowledge when solving typical hotel management problems. In a crosssectional study, data were collected from first-, fourth-, and eighthsemester students and compared with experts who had seven to ten years of experience working as hospitality managers. Three typical hospitality management cases were used to measure the way in which participants with different levels of education and experience cognitively represented the cases. Participants' recall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Managers responsible for making pricing and revenue decisions should always step back and consider whether the choices they make are right for their unit, based on its own capabilities, customers and service levels. As discussed in recent research by Wilson-Wünsch et al (2015), managers should develop the ability to turn facts from competitor data into higher levels of development knowledge in order to set the right price, and as Kimes (2011) predicted this requires analytical approaches to revenue management. What is perhaps fascinating and worthy of further investigation is that the industry's reaction has not necessarily been to build analytical skills, but to collect yet more data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Managers responsible for making pricing and revenue decisions should always step back and consider whether the choices they make are right for their unit, based on its own capabilities, customers and service levels. As discussed in recent research by Wilson-Wünsch et al (2015), managers should develop the ability to turn facts from competitor data into higher levels of development knowledge in order to set the right price, and as Kimes (2011) predicted this requires analytical approaches to revenue management. What is perhaps fascinating and worthy of further investigation is that the industry's reaction has not necessarily been to build analytical skills, but to collect yet more data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Moslehpour, Altantsetseg, Mou, and Wong [36], suggested leadership facilitates processes important in fostering (a) supportive work climates, (b) positive employee attitudes, and (c) commitment to organizational change. Wilson-Wünsch, Beausaert, Tempelaar, and Gijselaers [37] confirmed that leaders' knowledge and experience are a significant factor in the food service industry's organizational performance. Sipe [38] added that experienced leaders promote new ideas within organizations, which increases employee empowerment.…”
Section: Leadershipmentioning
confidence: 92%
“…Research into the hospitality industry has shown that knowledge developed at educational institutions often does not match the knowledge used in practice (Spowart, 2011;Costen et al, 2010;Ricci, 2010). Soft skills, for example, are reported to be vital for a hospitality manager's success (Wilson-Wünsch et al, 2015;Tews et al, 2011;Phelan and Mills, 2010;Chung-Herrera et al, 2003), but these are rarely developed reflectively in higher education settings.…”
Section: Hospitality Management and Educationmentioning
confidence: 99%